ANDROID APPLICATION DESIGN BASED ON COMPUTER SCIENCE ACADEMY TERNATE COURSE SCHEDULING - Albaar, Muhammad Ridha; Gufran, Kasyif; Syakdiyah, Halimatus (POLITEKNIK SAINS DAN TEKNOLOGI WIRATAMA MALUKU UTARA, 2025)
The provided introduction highlights the pressing issue faced by AIKOM Ternate due to the absence of an efficient scheduling system, leading to recurrent student rescheduling challenges at the beginning of each semester. The development approach involves the utilisation of a Use Case Diagram to illustrate the comprehensive course scheduling process, encompassing initial scheduling, learning activities, and examination schedules. Additionally, an Entity-Relationship Diagram (ERD) featuring four tables is crafted to underpin the creation of a robust database for the application. The scheduling system primarily addresses the coordination of space, time, and classes at AIKOM, emphasising the prevention of conflicts with both lecturers and students. The Android application's user interface is tailored to streamline the scheduling process, delivering a personalised output schedule that details courses explicitly. The efficacy of the application is intricately linked to the performance of the BAAK schedule concierge service, which plays a pivotal role in entering accurate data into the central database. It is crucial to note that the application's ability to furnish timely and precise schedule information hinges on the consistent and reliable execution of data updates by the BAAK; any lapses in this process result in a lack of updates within the application.Keyword: Android, Schedule, Design, Use Case Diagram, AIKOM